Letrozole Treatment of Precocious Puberty in Girls with the McCune-Albright Syndrome: A Pilot Study - Feuillan, Penelope; Calis, Karim; Hill, Suvimol; Shawker, Thomas; Robey, Pamela Gehron; Collins, Michael T. (The journal of clinical endocrinology and metabolism, 2007)
Context: Girls with McCune-Albright syndrome (MAS) and related disorders have gonadotropin-independent precocious puberty due to estrogen secretion from ovarian cysts. Their puberty does not respond to GnRH agonist therapy, and short-acting aromatase inhibitors have had limited effectiveness. Objective: Our objective was to assess the effectiveness of the potent, third-generation aromatase inhibitor letrozole in decreasing pubertal progression in girls with MAS and to assess the response of indices of bone turnover associated with the patients’ polyostotic fibrous dysplasia. Design: Subjects were evaluated at baseline and every 6 months for 12–36 months while on treatment with letrozole 1.5–2.0 mg/m2·d. Setting: This was an open-label therapeutic trial at a single clinical center. Patients: Patients included nine girls aged 3–8 yr with MAS and/or gonadotropin-independent puberty. Main Outcome Measures: Measures included rates of linear growth, bone age advance, mean ovarian volume, estradiol, episodes of vaginal bleeding, and levels of the indices of bone metabolism: serum osteocalcin, alkaline phosphatase, urinary hydroxyproline, pyridinoline, deoxypyridinoline, and N-telopeptides. Results: Girls had decreased rates of growth (P ≤ 0.01) and bone age advance (P ≤ 0.004) and cessation or slowing in their rates of bleeding over 12–36 months of therapy. Mean ovarian volume, estradiol, and indices of bone metabolism fell after 6 months (P ≤ 0.05) but tended to rise by 24–36 months. Uterine volumes did not change. One girl had a ruptured ovarian cyst after 2 yr of treatment. Conclusions: This preliminary study suggests that letrozole may be effective therapy in some girls with MAS and/or gonadotropin-independent precocious puberty. Possible adverse effects include ovarian enlargement and cyst formation.